Increasing the Efficiency of Return Transportation Documents: Case Study of CAINIAO SMART LOGISTICS NETWORK (THAILAND) CO., LTD (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purpose of this study is to explore the problems existing in the document management in the logistics process of Qidi Intelligent Logistics Network (Thailand) Co., Ltd., and to design more effective process improvement schemes. The research sample group consists of 10 operators, who are responsible for the different links of the IELTS test document management process, the preparation of work orders, the review of documents before shipment and the collection of evidence documents after transportation. This study adopts the method of Participatory Action Research (PAR), which is divided into three periods. The research contents include problem analysis, plan improvement, implementation and evaluation, and qualitative and quantitative data collection methods, including interviews. The results of fault state analysis based on fishbone diagram tool show that there are four main reasons for document management errors: (1) personnel-lack of understanding of the sequence, steps and details of documents; (2) workflow-redundancy and nonstandard; (3) Tools-lack of clear document monitoring system; (4) Working environment-lack of auxiliary tools for system control and document status tracking. Based on this analysis, the concept of visual control is applied to the design of functional support system, such as: using color to display document status; Checks designed for pre-delivery verification; Mark warnings at risk points; After the implementation, the document storage space is systematically improved. 25 times a month, only 0 times left. 76 times a month, a decrease of 93%. This reflects the efficiency of the new process design, which can reduce the loss of tasks that need to be solved repeatedly and significantly improve the speed of customer service.